On convergence of difference schemes of high accuracy for one pseudo-parabolic Sobolev type equation - Aripov, M.M.; Utebaev, D.; Kazimbetova, M.M.; Yarlashov, R.Sh. (Bulletin of the Karaganda University. Mathematics Series, 2023)
Difference schemes of the finite difference method and the finite element method of high-order accuracy in time and space are proposed and investigated for a pseudo-parabolic Sobolev type equation. The order of accuracy in space is improved in two ways using the finite difference method and the finite element method. The order of accuracy of the scheme in time is improved by a special discretization of the time variable. The corresponding a priori estimates are determined and, on their basis, the accuracy estimates of the proposed difference schemes are obtained with sufficient smoothness of the solution to the original differential problem. Algorithms for the implementation of the constructed difference schemes are proposed.